1992
DOI: 10.2307/2937317
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Faunal Interactions and Effects on Litter Nitrogen and Decomposition in Agroecosystems

Abstract: We conducted field experiments to test the general hypothesis that the composition of decomposer communities and their trophic interactions can influence patterns of plant litter decomposition and nitrogen dynamics in ecosystems. Conventional (CT) and no—tillage (NT) agroecosystems were used to test this idea because of their structural simplicity and known differences in their functional properties. Biocides were applied to experimentally exclude bacteria, saprophytic fungi, and microarthropods in field exclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
187
2
5

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 540 publications
(204 citation statements)
references
References 71 publications
10
187
2
5
Order By: Relevance
“…This was particularly surprising since high residue C returns from CW were expected to support more microbial biomass. In Biederbeck et al's (2005) tillage-based study, differences in MB-C between CW and F-W systems were related to differences in the bacterial fraction of MB-C. No-till systems likely rely more heavily on fungal, rather than bacterial decomposers (Beare et al 1992). The SIR method we used to estimate MB-C may not detect slow-responding fungal MB-C fractions as well as the fumigationextraction method (Wallenstein et al 2006) used by Biederbeck et al (2005).…”
Section: Discussionmentioning
confidence: 97%
“…This was particularly surprising since high residue C returns from CW were expected to support more microbial biomass. In Biederbeck et al's (2005) tillage-based study, differences in MB-C between CW and F-W systems were related to differences in the bacterial fraction of MB-C. No-till systems likely rely more heavily on fungal, rather than bacterial decomposers (Beare et al 1992). The SIR method we used to estimate MB-C may not detect slow-responding fungal MB-C fractions as well as the fumigationextraction method (Wallenstein et al 2006) used by Biederbeck et al (2005).…”
Section: Discussionmentioning
confidence: 97%
“…Soil organic matter decay induced by tillage is related to soil temperature, soil moisture, and the amount and quality of soil organic carbon (Zhang et al, 2011;Heal et al, 1997;Schomberg and Steiner, 1997;Beare et al, 1992). But, some researchers have shown higher emissions under NT relative to tilled plots attributed to decomposition of old surface residues (Oorts et al, 2007;Soane et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Tillage induces the loss of C as CO 2 by breaking up soil aggregates and exposing the protected organic matter to microbes. Tillage also incorporates and mixes residues, improving aeration, which can lead to additional C losses by maximizing soil-residue contact compared with no-residue incorporation (Jacinthe and Lal, 2005;Six et al, 1999).Soil organic matter decay induced by tillage is related to soil temperature, soil moisture, and the amount and quality of soil organic carbon (Zhang et al, 2011;Heal et al, 1997;Schomberg and Steiner, 1997;Beare et al, 1992). But, some researchers have shown higher emissions under NT relative to tilled plots attributed to decomposition of old surface residues (Oorts et al, 2007;Soane et al, 2012).…”
mentioning
confidence: 99%
“…According to Aoyama et al (2000), the proportion of C and N mineralized by the soil microflora was greater in macroaggregates than in microaggregates. Beare et al (1992) observed, in soils managed under zero tillage system, that the mineralization activity of C was higher than in soils under conventional tillage systems. These results suggest that the microbial biomass metabolizes more easily the N and C present in the organic matter of the macroaggregates.…”
Section: Introductionmentioning
confidence: 83%
“…In accordance with these results, Videla et al (1996), Ferrari et al (1997) and Henriksen and Breland (1999) found that biomass was the only parameter that did not reflect the changes induced by nitrogen fertilization in the mineralization of organic matter. However, Beare et al (1992) proposed that fumigation with chloroform was not the most suitable approach to use when the soils had an important contribution from organic wastes as occurs in f ield crops under zero tillage. Therefore, factors other than N were probably responsible of the evolution of the soil biomass such as the availability of phosphorus or other nutrient elements and also the methodology used.…”
Section: Discussionmentioning
confidence: 99%